How do EFL textbooks evaluate countries? Discursive and production perspectives - Watanabe Hideo (Journal of Language and Cultural Education)
This article examines evaluations of entities associated with countries in English language textbooks for junior high school students in Japan. Drawing on an APPRAISAL analysis and interviews, the study explores how evaluations of national entities are realized in the textbooks. Eighteen textbooks were analyzed, and three interviews were conducted, one with a textbook writer and two with textbook editors. The findings reveal that the English language textbooks evaluated entities associated with Japan in a positive light much more frequently than those related to other countries. This was realized by the writer and editors’ intention that the textbooks be used to teach aspects of Japanese culture and to nurture learners’ diverse perspectives toward countries and their cultures.